Teachers’ attitude towards education for sustainable development: A descriptive research - Joshith Vazhayil Peedikayil; Vrinda Vijayan; Thiyagu Kaliappan (International Journal of Evaluation and Research in Education (IJERE), 2023)
Teachers are the torch bearers of sustainable development, promoting social change and maintaining balance between two important concepts development and sustainability. They have a pivotal role in promoting education for sustainable development (ESD) perpetuating social change leading to progressive development and a futuristic growth in the society. ESD is one of the millennium development goals acknowledged globally and need to get practiced widely. Teachers play prominent role in inculcating the knowledge, spreading values, and enriching skills that are needed for sustainability to cope with the change in attributes of workplace. The central theme of the study was to determine the attitude of high school teachers concerning ESD. For this, the normative survey method (N=150) was used to collect data. The data were collected by an attitude scale entitled “ESD attitude scale”. This investigation examined teachers’ attitude towards ESD based on teachers’ gender, subject of teaching, and type of management of the institution. To achieve the objectives of the study, item-based assessment with percentage analysis, t-values and F-values were calculated. Research findings showed that teachers have a favorable attitude towards ESD. Gender and management of the institution were not found to change attitudes towards ESD of high school teachers, whereas the subject of teaching was found to change the same. With these pieces of evidence from the present study, educationalists can reform the existing high school education system for sustainable development.